Advanced Mechanics of Piezoelectricity - Qin, Qing-Hua.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
"Advanced Mechanics of Piezoelectricity" presents a comprehensive treatment of piezoelectric materials using linear electroelastic theory, symplectic models, and Hamiltonian systems. It summarizes the current state of practice and presents the most recent research findings in piezoelectricity. It is intended for researchers and graduate students in the fields of applied mechanics, material science and engineering, computational engineering, and aerospace engineering. Dr. Qinghua Qin is a professor at the School of Engineering, Australian National University, Australia.
Introduction to Piezoelectricity -- Mathematical Foundation -- Piezoelectric Fibre Pull-Out and Push-Out -- Trefftz Method for Piezoelectricity -- Symplectic Method for Piezoelectricity -- Saint-Venant Decay Problems in Piezoelectricity -- Penny-Shaped Crack -- Singularity in Functionally Graded Piezoelectric Wedges.
Keywords: Engineering; Mathematics; Mechanics, applied; Mechanical engineering; Civil engineering; Engineering; Mechanical Engineering; Theoretical and Applied Mechanics; Applications of Mathematics; Civil Engineering